2017
DOI: 10.1007/s11250-017-1323-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative diagnostic evaluation of OMP31 gene based TaqMan® real-time PCR assay with visual LAMP assay and indirect ELISA for caprine brucellosis

Abstract: Brucellosis is one of the leading causes of abortion in domestic animals that imposes costs on both economy and society. The disease is highly zoonotic and poses risk to animal handlers due to its zoonotic nature. It causes stillbirth, loss of kids and abortion in last term of pregnancy. Reproductive damage includes infertility in does and orchitis and epididymitis in breeding bucks, which result in high financial losses to farmers and the agriculture industry as a whole. It requires highly sensitive and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…The arrival of the real-time PCR has offered an opportunity to meet the requirements for rapid diagnosis (Saini et al, 2017) PCR offers a better method for swift and sensitive detection of microorganism. On the downside conventional PCR usually consists of 3 phases: DNA isolation, PCR amplification, and post-PCR analysis, which includes gel electrophoresis, hybridization and/or sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…The arrival of the real-time PCR has offered an opportunity to meet the requirements for rapid diagnosis (Saini et al, 2017) PCR offers a better method for swift and sensitive detection of microorganism. On the downside conventional PCR usually consists of 3 phases: DNA isolation, PCR amplification, and post-PCR analysis, which includes gel electrophoresis, hybridization and/or sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…For ruling out the presence of Brucella melitensis in preputial washings of breeding bucks, OMP31‐TaqMan ® probe PCR was used as per the reaction mix and thermal conditions described by Saini et al. (2017)…”
Section: Methodsmentioning
confidence: 99%
“…For ruling out the presence of Brucella melitensis in preputial washings of breeding bucks, OMP31-TaqMan ® probe PCR was used as per the reaction mix and thermal conditions described by Saini et al (2017) For Campylobacter spp., the oligonucleotides used are F: 5´-T GTCGTCAGCTCGTGTCGTG-3´ and R: 5´-TCTACGATTACTAGCGATT CCG-3´in a final 20 μl reaction mix to amplify a 276 bp PCR product (Beena et al, 2017). While, the PCR was performed for Coxiella burnetii using the 10 picomole each primers trans1: 5-′TATGTATCCACCGTAGCCAGTC-3′ and trans2: 5-′CCCAACAACACCTCCTTATTC-3′ to generate a 687bp PCR amplicon (Berri, Laroucau, & Rodolakis, 2000).…”
Section: Molecular Detection Of Microorganism Through Preputial Swabmentioning
confidence: 99%
“…Apart from the above discussed novel real time PCR assays, a lot of work has been done so far on the validation aspect of these real time PCR assays in different countries (Al Dahouk et al, 2007;Queipo-Ortuno et al, 2008;Amoroso et al, 2011;Doosti and Dehkordi, 2011;Kumar et al, 2015;Mukherjee et al, 2015;Awwad et al, 2016;Kumar et al, 2017;Saini et al, 2017 andPatel et al, 2018). All these studies have found real time PCR as fast, sensitive and reliable tool for early detection of causative organism in the biological samples so that control and eradication programmes can be adopted as early as possible to minimise the losses to animal husbandry sector.…”
Section: Real-time Pcrmentioning
confidence: 99%